Analisis Pengaruh Kedekatan Anggota Komunitas Online yang Berdampak pada Hubungan di Dunia Nyata melalui Penggunaan Teknologi - Dika Esa Pramudya; Diah Priharsari; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The development of internet technology in the form of social media is a social network which is an online community that can allow users to be connected to each other. Traditionally, a community is a social group consisting of organisms that share the same environment and have the same attraction. The problem examined in this study is that members in the community have not yet established a closeness that encourages members to meet directly. In the study using Self Disclosure Theory to help answer the formulation of the problem. The purpose of the study was to determine the closeness of members to encourage face-to-face meetings and to know the role of technology. Data was collected qualitatively to members of the online community using the interview method. The data obtained from the interviews were analyzed using the coding analysis method which is included in the thematic analysis. The result of the research is the closeness of the members taken from the trust and intimacy factor according to the Self Disclosure theory. And the ease of the role of technology that creates the closeness of members. So that it can encourage members to meet in person.